Optimalisasi Pengembangan Motif Batik Melalui Difusi Inovasi Pada Komunitas Pengrajin di Desa Bawangan - Baiq Tuhfatul Unsi; Fina Auliya; Lutfi Khanifah; Faradila Amalia (LP3M IAIFA Kediri, 2026)
This community service project aimed to optimize the development of batik motifs through the diffusion of innovation approach among artisans in Bawangan Village, Jombang Regency, East Java. The main challenges included limited motif variation, the use of synthetic dyes that pollute the environment, and weak access to digital markets. The project was implemented using the Participatory Action Research (PAR) method, emphasizing active artisan participation in problem identification, training, mentoring, and evaluation. The results indicated improved design skills with the creation of eight new motifs inspired by local flora and fauna, a 30% reduction in synthetic dye usage through the adoption of eco-friendly dyes, and enhanced digital promotion capacity that generated external orders. Pre–post evaluation showed a 52% increase in artisans’ design comprehension. This project highlights the importance of collaboration among universities, local government, and artisan communities to strengthen cultural identity and enhance the global competitiveness of batik.